Análisis a los Estados Financieros de “Alpisur Cía. Ltda.” de la ciudad de Loja Período 2020 – 2021 - Loarte Cuenca, Mercedes Elizabeth (2023)
The present research work titled "Analysis of the Financial Statements of Alpisur Cia. Ltda in Loja city for the period of 2020-2021" was undertaken to fulfill the degree requirement for Engineer in Accounting and Auditing in accordance with the Academic Regulations of the Universidad Nacional de Loja. The main objective of this study was to evaluate the economic and financial condition of the company using both vertical and horizontal analysis and financial indicators. The purpose of this analysis was to generate information on profitability and indebtedness, in order to make informed decisions that would contribute to the enhancement of the company's management practices. Based on the financial statements, explanatory notes, and other gathered information, the financial statements were obtained, reviewed, and restructured to conduct an analysis of the economic and financial structure. The analysis revealed that the current assets accounted for the highest proportion of assets, representing 79.58% and 83.80% in 2020 and 2021, respectively. This pattern was due to the company's commercial activities, with financial assets and inventory of merchandise being the predominant values in both periods. As for the horizontal analysis, inventories showed the greatest increase, at 73.43%, driven by the demand resulting from the post-COVID pandemic economic recovery. In terms of its economic structure, the cost of sales and production contributed the most, accounting for 84.40% in 2020 and 88.69% in 2021. These high costs have a negative impact on the company's profitability. Consequently, financial indicators were applied to measure the economic and financial situation, determining that the company has sufficient liquidity levels to continue its commercial activities. However, it was also found that the degree of indebtedness is high in both years, averaging around 80%, indicating that the company is largely financed by its creditors. As for the profitability ratio, the results are low, as a net profit of approximately 0.02 and 0.007 cents is generated for every dollar in sales in 2020 and 2021, respectively. This shows that in the last period, the company did not generate optimal benefits from the investment made, due to the high level of costs and expenses. Finally, a financial analysis report was prepared that presents a summary of the results obtained. The report establishes conclusions and recommendations for addressing the identified deficiencies in order to provide guidance for making informed decisions that will benefit the company.